Highly Selective Synthesis of Acrylic Acid from Lactide in the Liquid Phase. Issue 17 (18th July 2018) - Nagengast, Jens; Hahn, Simon; Taccardi, Nicola; Kehrer, Matthias; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob
Abstract: A new reaction system for the highly selective, hydrobromic acid catalyzed conversion of lactide into acrylic acid under mild conditions is reported. The applied liquid reaction system consists of a temperature‐stable bromide‐containing ionic liquid and 2‐bromopropionic acid as a source of dry HBr, with no volatile organic solvent being used. This allows for the in situ removal of the formed acrylic acid, leading to an unmatched acrylic acid selectivity of over 72 % at full lactide conversion. Accounting for leftover reaction intermediates on the way to acrylic acid, which could be recycled in an elaborate continuous process, the proposed reaction system shows potential for acrylic acid yields well above 85 % in the liquid phase. This opens new avenues for the effective conversion of biogenic lactic acid (e.g., obtained by fermentation from starch) to acrylic acid. The resulting bio‐acrylic acid is a highly attractive product for, for example, the diaper industry, where we expect consumers to be especially sensitive to aspects of sustainability. Abstract : Acrylic acid from renewables : An innovative liquid‐phase process is demonstrated for the conversion of lactide, and therefore its biogenic raw material lactic acid, to acrylic acid at mild temperatures and decreased pressures with outstanding selectivities. The applied liquid reaction system consists of a temperature‐stable bromide‐containing ionic liquid and 2‐bromopropionic acid as a source of dry HBr, with no volatile organic solvent being used.